ANALISIS TEGANGAN ADHESIVE SINGLE LAP JOINT AKIBAT PENAMBAHAN LUBANG MENGGUNAKAN SOFTWARE ANSYS - PRAYOGO, VEDI; ALI (e-Proceeding FTI, 2024)
This single lap joint adhesive joint is widely used in the field and is simple in terms of its manufacture. Adhesive connection is a connection that is not only for metal joining and can be used to connect two objects with different materials. My research discusses the adhesive stress for single lap joints due to holes and the addition of holes to reduce the concentration of stress that occurs in the main hole, my analysis or simulation in calculations to calculate the stress that occurs using Ansys workbench 2020 software. The modeling variations I used were variations without holes, the presence of holes and there were additional holes by varying the addition of holes 8 mm to 14 mm in diameter and I also varied the adhesive surface with variations of 3 kinds of roughness with roughness number 240 (6.28μm), roughness number 120 (12.29 μm) and roughness number 60 (20.32 μm) using solidworks 2018. Epoxy type adhesive material (E = 12960 MPa ѵ = 0.34). In this Ansys simulation, the load that works on a single lap joint is an axial load, for the modeling above, the stress results that occur. For variations without holes in the presence of holes, the stress is reduced, this is because the cross-sectional area of the bush is shrinking. With the addition of holes with different variations, the stress is reduced in diameter by 15 mm in all variations. The greatest reduction occurred in the variation of the 14 mm diameter hole so that the stress concentration was reduced by 18.89%. With the variation of the roughness value above, the stress increases with an increase in the roughness. So with the addition of holes it can reduce the concentration of stress. From the results of my research data, it turns out ththat it is more effective with the addition of holes because the stress concentration is reduced. Abstrak Sambungan perekat single lap joint ini banyak dipakai dilapangan dan sederhana dalam hal pembuatannya. Sambungan adhesive merupakan sambungan yang tidak hanya untuk logam penyambungannya dan bisa dipakai untuk menyambungkan dua benda dengan material yang berbeda. Penelitian saya ini membahas tentang tegangan adhesive untuk single lap joint akibat adanya lubang dan adanya penambahan lubang untuk mengurangi konsentrasi tegangan yang terjadi di lubang utama, analisis atau simulasi saya dalam perhitungan untuk mengitung tegangan yang terjadi menggunakan software Ansys workbench 2020. Variasi pemodelan yang saya gunakan variasi tanpa lubang, adanya lubang dan ada lubang tambahan dengan memvariasikan penambahan lubang diameter 8 mm sampai 14 mm dan saya variasikan juga permukaan adhesive dengan variasi 3 macam kekasaran dengan nomor kekasaran 240 (6,28 μm), nomor kekasaran 120 (12,29 μm) dan nomor kekasaran 60 (20,32 μm) menggunakan solidworks. Material adhesive jenis epoxy (E = 12960 MPa ѵ = 0,34). Pada simulasi Ansys ini beban yang bekerja pada single lap joint adalah beban axial, untuk pemodelan diatas didapatkan hasil tegangan yang terjadi. Untuk variasi tanpa lubang dengan adanya lubang maka tegangannya berkurang hal ini disebabkan karena luas penampang semakain mengecil. Dengan adanya penambahan lubang dengan variasi yang berbeda maka tegangannya berkurang di diameter 15 mm pada semua variasi. Pengurangan terbesar terjadi pada variasi lubang diameter 14 mm sehingga konsentrasi tegangannya berkurang sebesar 18,89%. Dengan variasi nilai kekasaran diatas maka tegangannya naik dengan kenaikan kekasarannya. Jadi dengan penambahan lubang itu bisa mengurangi konsentrasi tegangan. Dari hasil data penelitian saya ternyata lebih efektif dengan penambahan lubang karena konsentrasi tegangannya berkurang.